The role of mandatory cost audit in enhancing trust: the case of India - Chatterjee, Bikram; Mir, M. (Emerald Group Publishing Limited, 2006)
Purpose – The purpose of this paper explores whether cost audits as governance mechanism affected the trust of the users of financial statements and whether they provide the benefits intended by regulators. Design/methodology/approach – The research method involved unstructured open-ended face-to-face interviews with cost auditors in practice, mid- to high-level accounts and finance executives of companies and investors. Twenty-three interviews were conducted over a five-week period from December 2004 to January 2005 in Kolkata city of India. The selection of respondents was purposive, to explore the attitudes of these three groups towards mandatory cost audit. Findings – Mandatory cost audit in India has not enhanced the level of trust of investors and preparers of financial statements also have the opinion. It has not brought those benefits expected by regulators. Research limitations/implications – It is suggested following the findings of this paper that future research should carefully consider the usefulness and cost and benefit aspects of the mandatory cost audit in India. Originality/value – This is a pioneering study providing an in-depth analysis of mandatory cost auditing in India.